Study on the Spatial Distribution of Argon Bubbles in a Steel Slab Continuous Casting Strand. Issue 4 (28th October 2021) - Liu, Zhentong; Zhang, Lifeng; Zhou, Haichen; Chen, Wei
Abstract : The spatial distribution of argon bubbles in an 1800 mm × 230 mm continuous casting strand under different casting speeds and argon flow rates are studied through the numerical simulation using the Euler–Euler‐multiple‐size‐group approach. The calculated fluid flow is validated with water modeling and nail board measurements of industrial trials. Argon bubbles with diameter of 2 mm are injected into the submerged entry nozzle (SEN). The speed of the molten steel near the SEN decreased with the casting speed increasing and increased with the argon flow rate increasing. Most of argon bubbles are larger than 4.5 mm inside the mold at the casting speed of 0.6 m min −1 and the argon flow rate of 18 NL min −1 . The breakup rate of bubbles inside the mold increased with the increasing of the casting speed and the coalescence rate increased with the increasing of the argon flow rate. The coalescence and breakage of argon bubbles inside the mold mainly occurred during the rising of bubbles to the top surface and the moving of bubbles with the steel jet to the narrow face. The average diameter of bubbles decreased when the casting speed increased and the diameter increased when the argon flow rate increased. Abstract : The spatial distribution of argon bubbles inside the mold under different casting speeds and argon flow rates are studied through the numerical simulation using the Euler–Euler‐multiple‐size‐group approach. The coalescence and breakage of bubbles mainly occurred during the rising of bubbles to the top surface and the moving of bubbles with the steel jet to the narrow face.